DEVELOPMENT OF A BOOK CREATOR BASED E-MODULE TO SUPPORT DIFFERENTIATED LEARNING IN THE ACCOUNTING CYCLE MATERIAL FOR SERVICE COMPANIES AT STATE VOCATIONAL HIGH SCHOOL 10 SURABAYA - Novitasari, Vina Diah; Hakim, Luqman (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This development research produces a product in the form of an e modul based on a book creator. The purpose of this study is to describe the process of developing an e-module, analyze the feasiblity of the e-module product, and determine the response of students to the use of an e-module based on a book creator as a supporter of differentiated learning on the material of the accounting cycle of service companies. This development research uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, evaluation. The subjects in this study were students of class X Accounting at SMK Negeri 10 Surabaya. The results of the study showed that the average results of the e-module feasibility obtained from experts were with details of the average percentage of feasilbility by material experts of 92%, langage experts 95%, and graphic experts of 94%. The application of the e-module product developed for students received a very good response. This is supported by the average percentage of student responses of 95%. Based on these results, it can be concluded that the e module based on a book creator as a supporter of differentiated learning on the material of the accounting cycle of service companies is considered feasible and can be used in the learning process.